Antibiotic prophylaxis for elective caesarean section - a clinical audit in tertiary care teaching hospital - Sowmya K; Suma KB (Barpeta Obstetrics and Gynaecological Society, 2023)
Objective: The objective of the study was to analyse whether an audit, formulating policies and reaudit will help to improve prophylactic antibiotic usage and increase uniformity among women undergoing elective LSCS. Methodology: A retrospective case note review was performed for all elective caesarean section occurring over a 3 month period. Guidelines were introduced to address deficiencies and the reaudit was done. Results: During the study total of 204 pregnant women underwent elective LSCS out of which 96 in where in audit cycle and 108 in reaudit group. Prophylactic antibiotic prophylaxis administration was 38.5% v/s 89.8% (audit v/s reaudit group). Out of those who received antibiotic in audit group 40% (15 cases) received antibiotic within 1 hour whereas in reaudit group 79 (81.4%) women received antibiotic within 1 hour. The antibiotic usage in the audit group varied from amoxicillin clavulunic acid to cefoperazone sulbactam to cefotaxime which was mainly based on the operating surgeon's preference (54% v/s 45.9%). In the reaudit group majority of the women received amoxicillin clavulunic 1.2 gm IV /Inj cefotaxime (89% v/s 10.3%). Conclusion: Conducting an audit on usage of prophylactic antibiotic in women undergoing elective LSCS will help to assess the antibiotic usage. Formulating an antibiotic policy for prophylaxis in women undergoing elective LSCS and conducting an reaudit is a simple but effective tool to improve prophylactic antibiotic usage.